IS CHEST X-RAY USEFUL IN EARLY DETECTION OF LUNG CANCER? : THE SYSTEMATIC REVIEW - Izuddin, Afif (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Introduction: In spite of expanding utilize of computed tomography (CT), chest X-ray remains the first-line examination for suspected lung cancer in essential care in Indonesia. This paper point to assess the affectability of chest X-ray for recognizing lung cancer in symptomatic individuals. Method: This study using systematic review that search using keywords Lung Cancer and Chest X-Ray in Google Scholar, PubMed, and CrossRef. After final screening the author analysized 4 articles.. Result: chest X-ray falls flat to recognize lung cancer (at slightest at first) in >20% of individuals who are hence analyzed with lung cancer. All three of these considers were conducted in nations with broadly comparative essential care frameworks (Denmark, Britain, Republic of Ireland). Two of these considers were determined from essential care settings and, in spite of the fact that the remaining think about was from an auxiliary care radiology office, it is likely that numerous of the chest X-rays performed come about from essential care referrals. Conclusion: In spite of the fact that there's a lack of prove, the highest-quality ponders propose that the affectability of chest X-ray for symptomatic lung cancer is as it were 77% to 80%. GPs ought to consider in case encourage examination is essential in high-risk patients who have had a negative chest X-ray.